Implementasi Metode Flash Dalam Meningkatkan Hafalan Santri Di Rumah Tahfidz Quran Center Mojokerto - Nur Hanifah, Basyasyah; Rozi, Syaikhu (Philosophiamundi, 2023)
Qur'an learning generally uses Qur'an reading and writing learning as a medium for understanding the Qur'an, reading repeatedly is believed to be able to make someone easy to memorize the Qur'an. But in this Qur'an Center institution found a new learning method, namely the flash method, this flash method uses media movements to make it easier for children to memorize the Qur'an quickly. In learning the Qur'an using this flash method, the plan is that it can be implemented classically and individually. If classical in one class achievements, ability levels, and age are the same. In knowing the quality of the students' memorization using this Flash method, the asatidz provide several criteria to assess the quality of the students' memorization, namely: Mumtaz, Jayyid and Dhoif which if detailed into numerical units are 85-100 for Mumtaz, 75-84 for Jayyid and 1-50 for Dhoif. The advantages and disadvantages of this flash method are that it is easier and more fun but only applies to children.Based on this background, the author is interested in conducting research with the aim of: 1) analyze the flash method. 2) analyze the implementation of the flash method in improving memorization. Based on its form, this research includes a type of qualitative research. The data collection method uses observation, interview, and documentation. Data analysis consists of the implementation of the flash method and the quality of students' memorization when memorizing using the flash method.